Characterization of pediatric aortic arch vascular rings - Ahmed Fareed Almoazen; Nader Abd EL-Monem Fasseh; Hosny M.A ELmasry (Wolters Kluwer Medknow Publications, 2020)
Background Vascular rings (VRs) are rare congenital anomalies of the aortic arch. Along with clinical data, several imaging techniques help to suspect VR. Flexible fiberoptic bronchoscopy (FFB) is also considered the main tool for diagnosis. Aim The aim of the study is to describe the clinical, radiological, and bronchoscopic features of pediatric aortic VRs. Patients and methods A total of 61 patients with VR were included in the study on the basis of computed tomography (CT) angiography. The included children were subjected to history taking, clinical examination, chest radiograph, CT chest with angiography, and FFB. Results This study included 61 children with vascular aortic rings. The median age of diagnosis in this study was 8.5 months (range, 2-23 months). Recurrent chest infection was the most common clinical manifestation (81.96%) followed by monophonic wheeze (60.65%) and stridor (57.37%). Double aortic arch was the most common type (34.4%) followed by innominate artery compression syndrome (18%) and left arch with aberrant right subclavian artery (14.7%). Chest radiography showed the correct diagnosis in seven (11.4%) cases, while CT angiography proved correct in 50 (81.9%) patients and FFB in 56 (91.8%) patients. Conclusion Prolonged or recurrent respiratory difficulties and/or dysphagia should alert the pediatrician to the possibility of a VR. Preferably, those children should be submitted to bronchoscopy.